Structural MRI study of Pareidolia and Visual Hallucinations in Drug–Naïve Parkinson’s disease - Masakazu Ozawa; Tomotaka Shiraishi; Hidetomo Murakami; Daisuke Yoshimaru; Asako Onda; Hiromasa Matsuno; Teppei Komatsu; Kenichi Sakuta; Kenichiro Sakai; Tadashi Umehara; Hidetaka Mitsumura; Hirotaka James Okano; et al. (Scientific Reports)
Abstract Visual hallucinations (VH) and pareidolia, a type of minor hallucination, share common underlying mechanisms. However, the similarities and differences in their brain regions remain poorly understood in Parkinson’s disease (PD). A total of 104 drug-naïve PD patients underwent structural MRI and were assessed for pareidolia using the Noise Pareidolia Test (NPT) were enrolled. Subcortical gray matter volume and cortical surface volume were analyzed using the FreeSurfer software. Structural analyses revealed associations between NPT scores and atrophy in the right thalamus, right hippocampus, right temporal cortex, and right orbitofrontal cortex in all PD participants. These results were almost the same after adjusting for right-handed 97 patients with PD. It is considered that hallucinations in patients with PD are related to altered integration of sensory input (bottom-up) and prior knowledge (top-down) within the visual system. Our findings indicate that pareidolia in PD involves both bottom-up (thalamus and temporal cortex) and top-down (orbitofrontal cortex) processing disturbances; in contrast, VH predominantly involves bottom-up but not top-down regions. Understanding these distinctions could aid in the development of targeted interventions for hallucinations in patients with PD.